Inaccurate volume values in the discussion of Solomon"s sea in Yerushalmi Eruvin 1:5 - Zur, Uri (HTS teologiese studies, 2022)
Solomon’s sea (a brass basin used in the First Temple) was discussed in the Yerushalmi Talmud Eruvin 1:5 (as well as in BT Eruvin 14a-b), and it revolved around the shape of Solomon’s sea. However, inaccurate volume values of the basin were cited in the Yerushalmi. The aim of this article was to offer a new explanation for one problem arising in connection with these values. The setting of this study was the inaccurate volume values of the basin appearing in the Yerushalmi. The background of the issue at stake is the fact that Jewish scholars cannot accept that Scripture contains discrepancies (cf. BerR. 4:6). Our methods were to review the different explanations given by different commentators and to introduce a discussion by R. Avraham Ben Hiyya ha-Nassi and the Book of Tashbetz dealing with an explanation of verses related to the basin’s shape. We suggested a new idea based on the above-mentioned discussion: by reducing the basin’s width by one handbreadth as the verse states, one could reach exactly the values appearing in the Yerushalmi for the volumes of a squared basin and a circular basin. Based on our suggestion, one could settle the volume values appearing in the Yerushalmi without correcting them.Contribution: The key insight was that one could settle the volume values appearing in the Yerushalmi without correcting them. This insight was connected with the textual history of the Rabbinic literature, which exactly fit HTS’s scope.